Business Incubator Model in Higher Education: The Role of Islamic Finance - Tri Inda Fadhila Rahma; Nurbaiti; Siti Aisyah (Journal of Islamic Economics and Finance Studies, 2025)
The increasing unemployment rate among university graduates in Indonesia highlights the urgent need for higher education institutions to play an active role in fostering entrepreneurship. Business incubators (Inbis) have emerged as strategic initiatives to support students in developing entrepreneurial skills, accessing funding, and establishing sustainable startups. This study examines the role of business incubators in universities and the contribution of Islamic finance in supporting their growth. The research employs a benchmarking method by analyzing incubator programs at Universitas Brawijaya, Universitas Airlangga, and Universitas Negeri Surabaya. Findings indicate that university-based business incubators not only facilitate entrepreneurial education but also serve as financial and networking hubs that connect startups with potential investors. Additionally, Islamic finance provides alternative funding models, such as mudharabah and musyarakah, ensuring ethical financial practices that align with Sharia principles. The integration of business incubators and Islamic finance strengthens the entrepreneurial ecosystem in higher education, fostering financial independence among graduates while contributing to national economic development.   Meningkatnya tingkat pengangguran di kalangan lulusan perguruan tinggi di Indonesia menunjukkan perlunya peran aktif perguruan tinggi dalam mendorong pengembangan kewirausahaan. Inkubator bisnis (Inbis) telah muncul sebagai inisiatif strategis untuk membantu mahasiswa mengembangkan keterampilan kewirausahaan, memperoleh akses pendanaan, dan membangun startup yang berkelanjutan. Penelitian ini mengkaji peran inkubator bisnis di perguruan tinggi serta peran Keuangan Syariah dalam mendukung pertumbuhannya. Penelitian ini menggunakan metode benchmarking dengan menganalisis program inkubator di Universitas Brawijaya, Universitas Airlangga, dan Universitas Negeri Surabaya. Temuan penelitian menunjukkan bahwa inkubator bisnis berbasis kampus tidak hanya memfasilitasi pendidikan kewirausahaan, tetapi juga berfungsi sebagai pusat pendanaan dan jaringan yang menghubungkan startup dengan calon investor. Selain itu, pembiayaan syariah menyediakan model pendanaan alternatif, seperti mudharabah dan musyarakah, yang memastikan praktik keuangan etis yang sesuai dengan prinsip-prinsip syariah. Integrasi antara inkubator bisnis dan pembiayaan syariah memperkuat ekosistem kewirausahaan di perguruan tinggi, mendorong kemandirian finansial lulusan, serta berkontribusi pada pembangunan ekonomi nasional.